Analisis Rasio Keuangan Daerah untuk Menilai Kinerja Keuangan Pemerintah Daerah Nusa Tenggara Barat Tahun 2018 – 2022 - Ade Budi Setiawan; Siti Rachma; Haklima Bintang Wulandari; Pitriani Dwi Agustin; Ristya Cahya Khaerunissa; Nihlatul Muniroh; Laila Lutfiyyah Salsabila (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
Regional government financial performance is a strategic indicator for assessing the success of regional autonomy implementation, particularly in managing public finances in an effective, efficient, transparent, and accountable manner. This study aims to analyze the financial performance of the Government of West Nusa Tenggara Province (NTB) during the 2018–2022 period using a regional financial ratio analysis approach. The research employs a descriptive quantitative method utilizing secondary data obtained from the Budget Realization Reports (LRA) and the Regional Government Financial Statements (LKPD) that have been audited by the Audit Board of the Republic of Indonesia (BPK). The analysis is conducted by calculating regional financial ratios, including the financial independence ratio, the effectiveness ratio of Regional Original Revenue (PAD), the efficiency ratio of regional finances, the activity ratio (expenditure harmony), and the revenue growth ratio. The results indicate that the financial performance of the Government of West Nusa Tenggara Province has generally improved. The regional financial independence ratio falls within the participatory category with an average value of 57.81%, reflecting a gradual reduction in dependence on central government transfer revenues, particularly in 2022. The effectiveness ratio of PAD is categorized as moderately effective, with an average of 92.84%, although it fluctuates due to increases in revenue targets that were not fully matched by actual revenue realization. The regional financial efficiency ratio consistently remains in the efficient category, indicating the local government’s ability to control expenditures relative to revenues. Furthermore, the activity ratio analysis shows a shift in expenditure composition from operating expenditure toward capital expenditure, indicating an increased orientation toward development and long-term investment. The growth ratio reveals a significant increase in PAD in 2022, accompanied by a decline in transfer revenue growth.